Imitatio Dei in Maimonides' Guide of the Perplexed - Kreisel, Howard T. (AJS review, 1994)
There is probably no topic in Maimonides' philosophy more thoroughly explored than that of human perfection, many of the studies dealing explicitly with the notion of imitatio Dei. Maimonides' view of ultimate perfection has been interpreted alternatively as primarily either intellectual, political, ethical, or halakhic. Many have interpreted Maimonides as positing a harmonious combination of the contemplative life and the life of socially oriented activity—bios praktikos—despite the evident tension between the two.Others have explained the apparent inconsistency in Maimonides' approach in terms of the distinction between exoteric and esoteric doctrines. The appropriate texts in Maimonides' writings have been analyzed in detail, and the sources at his disposal have been discussed at length. The challenge facing the student of Maimonides' thought, however, lies not only in explicating the individual texts which deal in a direct manner with the topic, but also in identifying all the issues and texts which are relevant to the topic, as well as their sources, and how they are related.